22. Jahrestagung 17.bis 20. März 2014, Berlin : abstracts (Oldenbourg Wissenschaftsverlag GmbH, 2014)
Zeitschrift für Kristallographie. Supplement Volume 34 presents the complete Abstracts of all contributions to the 22nd Annual Conference of the German Crystallographic Society in Berlin 2014.
Keywords: Crystallography -- Congresses.; Quasicrystals -- Congresses.; elektronické knihy; electronic books